Racism and equality in the European Union - Bell, Mark, 1974- (Oxford : Oxford University Press, 2008)
Mark Bell explores the effect of anti-racism policies in topical areas of EU law and policy including employment, social inclusion, immigration, and the criminal law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Race discrimination -- Law and legislation -- European Union countries; Equality -- European Union countries